The Applicability of Using Parameters of the Autocorrelation Function in the Assessment of Human Balance During Quiet Bipendal Stance - Jacek Stodółka; Leszek Korzewa; Weronika Stodółka; Jarosław Gambal (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
The purpose of the study was to analyze the parameters of the autocorrelation function when assessing time series ground reaction force (GRF) signals during quiet standing. GRF in the three directions were recorded on two Kistler force plates during three 15-s trials in a sample of 82 (31 females and 51 males) participants. Autocorrelation was performed on the GRF data and four parameters characterizing the function were computed. Comparisons of the right- and left-foot parameter means showed significant differences in mediolateral GRF for the time of the function's decay to 0, magnitude of the derivative output, and mean decay velocity to the extremum. Significant correlations were observed among all parameters – weak correlations between the time of the function's decay to 0 and the time to the first extremum and strong correlations between the derivative output and mean decay velocity to the extremum. The analyzed autocorrelation function parameters can serve as a precise measure of the motor control process during quiet standing. The strong correlations observed between the four parameters indicate that they evaluate similar properties of the central nervous system as a regulator of balance maintenance.